Vivências acadêmicas: análise de fatores que interferem na experiência universitária - Goulart, Juliana Sonego (2017)
The present study aimed to identify the factors that influence in the academic experience. For that, an online questionnaire, Questionnaire of Academic Experiences (QAE-r), was applied to the students of two campuses of a Federal Institution in the countryside of the Rio Grande do Sul State. The campuses were chosen according to their area of formation, being one of the health area and another of the technology. The sample had 287 respondents, being these 61% female students and 39% male students. The presentation of the collected information is organized in two articles, the first one related to the description of the information concerning the dimensions that involve the academic experience, being these: personal, interpersonal, institutional, career and study. The second article focuses on correlational analysis, with an area division of concentration of the training and by period of course, the latter being divided into university entrance, intermediate phases and end of course. Data analysis presented a lower mean in the personal dimension and the larger in the career dimension. In the correlation analysis, the results pointed to differences related to the period of the course, being the largest numbers in the group that represented university admission. Regarding the area of concentration, the numbers of the correlation analysis of the dimensions presented some differences, and the health area presented significant correlations in all dimensions; Already in the area of technology, there was a decrease in the significant correlations, being that the ones of greater value are related to the career. Stand out the importance of studies that are of interest beyond the year of the student´s entry into the institution, as well as being more focused on issues related to the personal dimension. Other instruments can be used in order to collect more information about the academic reality regarding their experience. The institution presents an important role in the management of all the manifestations existing in its context, and it is interesting to investigate the way it looks at the experience of its students.